Analysis of Water Vapor Correction for CloudSat W-Band Radar - Josset, D.; Tanelli, S.; Hu, Y.; Pelon, J.; Zhai, Peng-Wang (IEEE, 2013)
We analyzed different models to estimate absorption at W-band by gaseous species by taking advantage of the collocated CloudSat-Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) measurements. We used the power backscattered by the surface in the green visible wavelength of the lidar of CALIPSO as a reference to infer CloudSat's 94-GHz ocean surface backscatter in clear air and infer the attenuation introduced by gaseous absorption. Different millimeter-wave propagation models (MPMs) and different sources to determine the profile of atmospheric thermodynamic state are used to estimate CloudSat attenuation. These estimates are compared to the observations to calculate the residual dispersion. We show here that we need to adjust the empirical constants of preexisting water vapor absorption models to minimize the dispersion. Our results indicate an overestimation of absorption by the water vapor continuum at 94 GHz in Liebe-based MPM. We also propose a new empirical model to better represent the absorption of the water vapor continuum near 94 GHz. When this model is used in combination with the Advanced Microwave Scanning Radiometer for the Earth Observing System water vapor path and the Global Modeling and Assimilation Office water vapor vertical profile distribution, it leads to the lowest dispersion of the data on a statistical basis (global data over one month). The improved model is expected to optimize water vapor correction applied to CloudSat data and, potentially, also to improve interpretation of brightness temperature measurements in the W-band (e.g., 85- and 98-GHz radiometric channels).